+0  
 
0
103
2
avatar

[1/5 (9)^5-4(9)^3+5(-7)]-[( 1/5 (-7)^5-4(-7)^3+5(-7)]

Guest Apr 24, 2017
Sort: 

2+0 Answers

 #1
avatar+6711 
0

[1/5 (9)^5-4(9)^3+5(-7)]-[( 1/5 (-7)^5-4(-7)^3+5(-7)]

 

\([\frac{1}{5}\cdot 9^5-4\cdot 9^3+5\cdot (-7)]-[\frac{1}{5}\cdot (-7)^5-4\cdot (-7)^3+5\cdot (-7)]\)

 

\(=[11809.8-2916-35]-[-3361.4+1372-35]\)

 

\(=[8858.8]-[-2024.4]\)

 

\(=10883.2\)

 

laugh  !

asinus  Apr 24, 2017
edited by asinus  Apr 24, 2017
 #2
avatar+89827 
+3

[1/5 (9)^5-4(9)^3+5(-7)]-[( 1/5 (-7)^5-4(-7)^3+5(-7)]

 

I am going to do it without a calculator!     laugh

 

\([\frac{ (9)^5}{5}-4(9)^3+5(-7)]\quad -\quad [\frac{ (-7)^5}{5}-4(-7)^3+5(-7)]\\ =[\frac{ (9)^5}{5}-4(9)^3-35]\quad -\quad [\frac{ -(7)^5}{5}+4*7^3-35]\\ =\frac{ (9)^5}{5}-4(9)^3-35 \quad +\quad \frac{ +(7)^5}{5}-4*7^3+35\\ =\frac{ (9)^5}{5}-4(9)^3 \quad +\quad \frac{ +(7)^5}{5}-4*7^3\\ =\frac{9^3}{5}(9^2-20) \quad +\quad \frac{ 7^3}{5}(7^2-20)\\ =\frac{729}{5}(61) \quad +\quad \frac{ 343}{5}(29)\\ =\frac{729}{5}(60)+ \frac{729}{5}+\quad \frac{ 343}{5}(30)-\frac{ 343}{5}\\ =729*12+ \frac{730}{5}-\frac{1}{5}+\quad 343*6-\frac{ 345}{5}+\frac{2}{5}\\ =729*12+ \frac{385}{5}+\quad 343*6+\frac{1}{5}\\ =729*12+ \frac{385}{5}+\quad 343*6+\frac{1}{5}\\ =729*12+77+\quad 343*6+\frac{1}{5}\\ =6*1458+77+\quad 343*6+\frac{1}{5}\\ =6*1801+77+\quad \frac{1}{5}\\ =10806+77+\quad \frac{1}{5}\\ =10883\frac{1}{5}\\ \)

Melody  Apr 24, 2017

7 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details